From The Daily Show to Last Week Tonight: A Quantitative Analysis of Discursive Integration in Satirical Television News. (4th July 2021) - Brugman, Britta C.; Burgers, Christian; Beukeboom, Camiel J.; Konijn, Elly A.
ABSTRACT: Satirical news shows constitute an innovative hybrid genre that mixes regular news and fiction. The discursive integration hypothesis posits that the defining characteristic of satirical news shows is that news and fiction elements are integrated such that boundaries between the preexisting genres have blurred. The current study quantitatively tests this hypothesis on both long-running American shows such as The Daily Show and more recent shows such as Last Week Tonight . We collected transcripts of fifteen satirical news shows, eleven regular news shows, and fourteen fiction shows from 2018 (9, 824, 249 words). Transcripts were automatically tagged for over fifty linguistic features to identify register dimensions, patterns in linguistic features unique to genres, which we used to determine the presence of discursive integration. Findings revealed that two-thirds of satirical news shows were indeed characterized by discursive integration (which we labeled "complete hybrids"), while one-third manifested through the already existing hybrid genre of opinionated news (which we labeled "hybrid-genre echoes"). These two categories of shows demonstrate the importance of genre hybridity for defining satirical news across different shows.